Sexism in the advertising discourse of Ukraine - Y. Khodachuk; Y. Maslova (Kazimierz Wielki University, 2021)
The article identifies the reasons for the use of sexist advertising in the Ukrainian media discourse and its impact on the formation of women's image and social well-being. Sexist advertising campaigns of Ukrainian organizations are analyzed.